Faktor-Faktor yang mempengaruhi Return Saham pada IDX BUMN20 periode 2016-2020 - Siska, Siska; Pusvikasari, Nila (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This research was conducted with the aim of examining the effect of the independent variables consisting of Current Ratio, Debt To Equity, Return On Equity, Total Asset Turnover, and Earning Per Share on the dependent variable, namely Stock Return. The population used in this study are state-owned enterprises (BUMN) listed on the Indonesia Stock Exchange during the 2016-2020 period. This study uses a purposive sampling method so as to produce 7 companies that meet the criteria. This study uses a random effect model. The results of this study indicate that Return on Equity and Earning per Share are positive affect to Stock Return then Debt to Equity Ratio, Current Ratio, Total Asset Turnover are negatively affect to Stock Return.